2022
DOI: 10.1055/a-1868-4918
|View full text |Cite
|
Sign up to set email alerts
|

IMPORTANCE of PRETREATMENT 18F-FDG PET/CT TEXTURE ANALYSIS in PREDICTING EGFR and ALK MUTATION in PATIENTS with NON-SMALL CELL LUNG CANCER

Abstract: Objective Identification of anaplastic lymphoma kinase (ALK) and epidermal growth factor receptor (EGFR) mutation types is of great importance before treatment with tyrosine kinase inhibitors (TKIs). Radiomics is a new strategy for noninvasively predicting the genetic status of cancer. We aimed to evaluate the predictive power of 18F-FDG PET/CT-based radiomic features for mutational status before treatment in non-small cell lung cancer (NSCLC) and to develop a predictive model based on radiomic features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently, the idea that imaging studies contain a great quantity of data, in the form of grey-level patterns, which are imperceptible to the human eyes, has become more and more interesting [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ]. These texture features, when correlated with clinical-pathological data and outcomes [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ], theoretically allow diagnostic and prognostic assessment [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. The assessment of textural characteristics, obtained by radiological images, which depend on mathematical analysis, such as histogram analysis, is called radiomics [ 163 , 164 , 165 , …”
Section: Common Postoperative Complicationsmentioning
confidence: 99%
“…Recently, the idea that imaging studies contain a great quantity of data, in the form of grey-level patterns, which are imperceptible to the human eyes, has become more and more interesting [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ]. These texture features, when correlated with clinical-pathological data and outcomes [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ], theoretically allow diagnostic and prognostic assessment [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. The assessment of textural characteristics, obtained by radiological images, which depend on mathematical analysis, such as histogram analysis, is called radiomics [ 163 , 164 , 165 , …”
Section: Common Postoperative Complicationsmentioning
confidence: 99%
“…Profiling the TIME phenotype aids in patient selection for immunotherapy. Agüloğlu ( 39 ) and Chang ( 40 ) predicted anaplastic lymphoma kinase (ALK) rearrangement and EGFR mutation status in NSCLC via radiomics models based on 18 F-FDG PET/CT images, assisting in targeted therapy decisions. Numerous studies have demonstrated the capability of 18 F-FDG PET/CT radiomics models to predict programmed death ligand-1 (PD-L1) expression in NSCLC ( 41 44 ).…”
Section: Progress In the Application Of Pet-related Radiomics In Lung...mentioning
confidence: 99%
“…Agüloğlu et al. ( 50 ) found that the NB machine learning algorithm established using the GLZLM_GLNU feature and clinical data contributed to the most successful prediction of EGFR mutations (AUC = 0.751). Shiri et al.…”
Section: Introductionmentioning
confidence: 99%